YES Problem: strict: f(x) -> s(x) f(s(s(x))) -> s(f(f(x))) weak: rand(x) -> x rand(x) -> rand(s(x)) Proof: Arctic Interpretation Processor: dimension: 2 interpretation: [0 -&] [s](x0) = [0 0 ]x0, [0 0] [f](x0) = [0 0]x0, [1 1] [rand](x0) = [3 3]x0 orientation: [0 0] [0 -&] f(x) = [0 0]x >= [0 0 ]x = s(x) [0 0] [0 0] f(s(s(x))) = [0 0]x >= [0 0]x = s(f(f(x))) [1 1] rand(x) = [3 3]x >= x = x [1 1] [1 1] rand(x) = [3 3]x >= [3 3]x = rand(s(x)) problem: strict: f(x) -> s(x) f(s(s(x))) -> s(f(f(x))) weak: rand(x) -> rand(s(x)) String Reversal Processor: strict: f(x) -> s(x) s(s(f(x))) -> f(f(s(x))) weak: rand(x) -> s(rand(x)) Matrix Interpretation Processor: dim=5 interpretation: [1 1 0 0 0] [0] [0 0 0 1 0] [0] [s](x0) = [0 0 0 0 0]x0 + [1] [0 1 0 1 0] [0] [1 0 0 0 0] [0], [1 1 0 0 0] [0] [0 0 0 1 0] [1] [f](x0) = [0 0 0 0 0]x0 + [1] [0 1 0 1 0] [1] [1 0 1 0 0] [0], [1 0 0 0 0] [1] [0 0 0 0 0] [0] [rand](x0) = [0 0 0 1 0]x0 + [1] [0 0 0 0 0] [0] [1 0 1 0 1] [1] orientation: [1 1 0 0 0] [0] [1 1 0 0 0] [0] [0 0 0 1 0] [1] [0 0 0 1 0] [0] f(x) = [0 0 0 0 0]x + [1] >= [0 0 0 0 0]x + [1] = s(x) [0 1 0 1 0] [1] [0 1 0 1 0] [0] [1 0 1 0 0] [0] [1 0 0 0 0] [0] [1 2 0 2 0] [2] [1 2 0 2 0] [1] [0 1 0 2 0] [2] [0 1 0 2 0] [2] s(s(f(x))) = [0 0 0 0 0]x + [1] >= [0 0 0 0 0]x + [1] = f(f(s(x))) [0 2 0 3 0] [3] [0 2 0 3 0] [3] [1 1 0 1 0] [1] [1 1 0 1 0] [1] [1 0 0 0 0] [1] [1 0 0 0 0] [1] [0 0 0 0 0] [0] [0 0 0 0 0] [0] rand(x) = [0 0 0 1 0]x + [1] >= [0 0 0 0 0]x + [1] = s(rand(x)) [0 0 0 0 0] [0] [0 0 0 0 0] [0] [1 0 1 0 1] [1] [1 0 0 0 0] [1] problem: strict: f(x) -> s(x) weak: rand(x) -> s(rand(x)) Arctic Interpretation Processor: dimension: 4 interpretation: [0 -& -& 0 ] [-& -& -& -&] [s](x0) = [-& -& -& -&]x0 [-& -& -& -&] , [3 0 0 3] [0 0 0 0] [f](x0) = [0 0 0 0]x0 [0 0 0 0] , [0 0 0 0] [0 0 0 0] [rand](x0) = [0 0 0 0]x0 [0 0 0 0] orientation: [3 0 0 3] [0 -& -& 0 ] [0 0 0 0] [-& -& -& -&] f(x) = [0 0 0 0]x >= [-& -& -& -&]x = s(x) [0 0 0 0] [-& -& -& -&] [0 0 0 0] [0 0 0 0 ] [0 0 0 0] [-& -& -& -&] rand(x) = [0 0 0 0]x >= [-& -& -& -&]x = s(rand(x)) [0 0 0 0] [-& -& -& -&] problem: strict: weak: rand(x) -> s(rand(x)) Qed